2004
DOI: 10.1111/j.0022-202x.2004.22339.x
|View full text |Cite
|
Sign up to set email alerts
|

The Prostaglandin E1 Analog Misoprostol Reduces Symptoms and Microvascular Arteriovenous Shunting in Erythromelalgia—A Double-Blind, Crossover, Placebo-Compared Study

Abstract: Based on previous experience with parenteral prostanoids, we studied the effect of misoprostol treatment, an orally administered prostaglandin E1 analog, in patients with erythromelalgia. Treatment with placebo was followed by treatment with misoprostol (0.4-0.8 mg per d), both for 6 wk. The patients (n=21) and a study nurse who administered the trial were blinded. The endpoints were change in pain and need for cooling and global assessment of the treatment. Following central body heat provocation, global skin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 25 publications
(32 reference statements)
0
13
0
Order By: Relevance
“…Mork et al, in a double-blind controlled placebo prospective study in 21 patients observed that the analogue of oral PGE1, misoprostol, given on a 0,4 a 0,8 mg/day for 6 weeks , determined a significant reduction of the pain symptoms and local erythema but this decrease did not persist and after three months of treatment no further continuation was required. 3 As the responses for the current available treatments varies a lot, it was chosen as a more conservative treatment for our patient who had been presenting long periods between the crises (5 years) and limited duration (two weeks) of the symptoms. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mork et al, in a double-blind controlled placebo prospective study in 21 patients observed that the analogue of oral PGE1, misoprostol, given on a 0,4 a 0,8 mg/day for 6 weeks , determined a significant reduction of the pain symptoms and local erythema but this decrease did not persist and after three months of treatment no further continuation was required. 3 As the responses for the current available treatments varies a lot, it was chosen as a more conservative treatment for our patient who had been presenting long periods between the crises (5 years) and limited duration (two weeks) of the symptoms. …”
Section: Discussionmentioning
confidence: 99%
“…1 Heat exposure, physical exercises, gravity and the use of stockings/socks and gloves can act as triggers of the symptoms or intensify the discomfort while cold causes discomfort relief. [3][4][5] The disease takes typically a chronic course and it is associated with a decrease in the quality of life and considerable morbidity. It differs from Lane's palmoplantar erythema or red palms syndrome -a congenital, familial and hereditary dysplasia characterized by persistent and symmetric redness, without subjective manifestations -due to the intermittent nature of the symptoms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prostaglandin and prostacyclin analogs with vasodilatory effects have been the subjects of two small RCTs in EM treatment of pain (n=12–21). Findings were that iloprost and misoprostol were associated with a reduction in symptoms and sympathetic dysfunction 7,34,35…”
Section: Pharmacotherapymentioning
confidence: 99%
“…A study by Mork et al [6] is the only double-blind, crossover, placebo-compared study of a drug in erythromelalgia. A study by Mork et al [6] is the only double-blind, crossover, placebo-compared study of a drug in erythromelalgia.…”
Section: • Prostaglandin Inhibitors Including the Potent Vasodilatormentioning
confidence: 99%